Visualisasi Data Pelayanan Dinas Kependudukan dan Pencatatan Sipil Kabupaten Ogan Ilir Menggunakan Dashboard Interaktif - Zhofiroh Khoirunnisa; Siti Sa'uda (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2025)
The Department of Population and Civil Registration of Ogan Ilir Regency faces challenges in managing service data due to non-integrated systems and manual reporting processes. These conditions hinder effective performance evaluation and increase the risk of inaccurate data recording. This study aims to develop an interactive service data visualization dashboard using Microsoft Power BI to support real-time monitoring and improve the clarity of service information. The dashboard development follows the ADDIE model up to the development stage to ensure alignment with user needs. The dataset used consists of 8,190 validated service records from the year 2024. The resulting dashboard displays key indicators, including total services, service divisions, service types, monthly trends, and interactive filters. The main contribution of this study lies in providing a structured and integrated visualization model that enhances service transparency and enables faster, data-driven decision-making within government agencies.